TUDUNG MANTO AND THREE COUNTRIES RELATIONS (INDONESIA-MALAYSIA-SINGAPORE): Introduction, Method, Results and Discussion, conclusion - Anastasia Wiwik Swastiwi; Desri Gunawan; Glory Yolanda Yahya; Gulmok Simbolon; Riko Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
Tudung Manto is a cloth that is usually used as a head covering and is a completeness of traditional clothing, especially for Malay women, Lingga Regency, Riau Islands. Tudung Manto has been designated as an Indonesian Intangible Cultural Heritage owned by Lingga Regency, Riau Archipelago. Tudung Manto has also been officially registered through the Ministry of Law and Human Rights under Law Number 19 of 2002 concerning the Protection of Creation in the Fields of Science, Arts and Literature. In the course of its history, Tudung Manto involved the role of Terengganu (Malaysia) and Singapore as suppliers of lametta (not gold and silver). Writing This study looks at the relationship between Lingga (Indonesia) and Terengganu (Malaysia) and Singapore in the cultural heritage of the manto tudung and its future prospects. The type of research used is qualitative research using a historical approach. Sources of data used are primary and secondary data sources. Data were obtained through searching archives and Malay manuscripts, interviews, observation and documentation studies. The results of this study show Tudung Manto's cultural heritage has the potential to open up an open space for dialogue mere-tightening the historical and cultural ties of Indonesia-Malaysia-Singapore relations. In the end, the tudung manto can be used as a tool for cultural diplomacy between Indonesia - Malaysia - Singapore and can open up opportunities for cooperation in other fields.